Analysis Of Knowledge And Attitude Fisherman In Environmental Management Participation in Coastal Area Of Palopo City - Asri Sakka Ambo Sakka (Universitas Cokroaminoto Palopo, 2021)
Environmental condition of the coastal area of Palopo City has long been damaged due to the behavior of the fishermen. The form environmental damage along the coastline of mangrove forests is extinct, slums and squalid neighborhoods due to organic, inorganic waste, and puddles of household sanitation waste. The Overcoming of problems measures the level of knowledge, attitudes, and participation of fishermen in managing their environment. Research purposes this is gain The description of the level of environmental knowledge together with attitudes towards the environment will affect the participation of fishermen in managing their environment so that it is suitable for occupation. This research was conducted of Penggoli Village and the Batupasi Village, Palopo City, with the number of research subjects as 75 people. Data were collected using test instruments knowledge, The questionnaire measures attitudes and participation. Data analysis uses regression analysis the basis for decision making regarding environmental knowledge and attitudes the environment, together have an effect on participation in environmental management, namely the addition of the knowledge score affects the participation score of 0.907 and the addition of the attitude score affects the participation score of 0.388.